Rolled-up nanotechnology: 3D photonic materials by design. (September 2016) - Böttner, Stefan; Jorgensen, Matthew R.; Schmidt, Oliver G.
Abstract: Rolled-up nanotechnology involves the deposition of strained material layers for subsequent release and relaxation into functional structures with applications spanning several disciplines. Originally developed for use with semiconductor materials, over the last decade the processes involved in rolled-up nanotechnology have been applied across a wide palette of materials resulting in applications (among others) in micro robotics, energy storage, electronics, and photonics. Here we highlight the key advancements and future directions in rolled-up photonics, focusing on the diverse demonstrations of rolled-up three-dimensional microresonators which enable integrated sensing, micro-lasing, and out-of-plane routing of light. Graphical abstract: